2D electrostatic simulation of the modulated electron beam interaction with inhomogeneous plasma - Anisimov, I.O.; Litoshenko, T.Eu. (Вопросы атомной науки и техники, 2006)
Electrostatic plasma simulation code for 2D rectangular geometry is presented. Main distinguishing feature of the code is its orientation on the beam-plasma interaction. The code and its graphical interface were developed using MATLAB programming language. Simulation results of inhomogeneous plasma interaction with modulated electron beams of different width are compared. In case of wide beam the front of Langmuir waves generated in point of local plasma resonance is planar and in case of thin beam (or ribbon beam) the front has approximately half-circular form.